Edukasi Jajanan Sehat Sebagai Upaya Mengoptimalkan Tumbuh Kembang Anak Usia 4-6 Tahun - Yessy Nur Endah Sary; Tutik Ekasari; Tri Iriyani; Nova Hikmawati; Iit Ermawati; Muthmainnah zakiyyah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Children with malnutrition or malnutrition tend to be vulnerable to disease and stunting. Providing nutrition or food intake to children must first be in accordance with the child's growth and development level, secondly it must be in accordance with economic and socio-cultural conditions, and thirdly its nutritional value must be balanced. The aim of this community partnership program is to increase the knowledge of parents who have children aged 4 to 6 years about what types of snacks are beneficial for the growth and development of early childhood. This activity consists of three stages. The first stage is preparation and pre-test, the second stage is providing education about healthy snacks, the third stage is post-test, analysis of increasing knowledge and reporting the results of activities. The results of the activity analysis indicate that there is an increase in parents' knowledge about healthy snacks after being provided with education. The implication of this community partnership program activity is that parents need to continuously obtain information from various sources about healthy snacks and continue to accompany and monitor the snacks consumed by children, so that optimal growth and development can be achieved.